2019
DOI: 10.1073/pnas.1813642116
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between structure and function during the hemostatic response to injury

Abstract: Extensive studies have detailed the molecular regulation of individual components of the hemostatic system, including platelets, coagulation factors, and regulatory proteins. Questions remain, however, about how these elements are integrated at the systems level within a rapidly changing physical environment. To answer some of these questions, we developed a puncture injury model in mouse jugular veins that combines high-resolution, multimodal imaging with functional readouts in vivo. The results reveal striki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 28 publications
8
71
0
Order By: Relevance
“…Amplification follows when adherent platelets sense the small amounts of thrombin via G-protein coupled protease-activated receptors (PAR) that induce a positive feedback loop in the platelet to catalyze factor V, VIII and XI activation on the platelet surface. In the propagation phase platelets are strongly activated and their increased surface area provides an assembly stage to scaffold prothrombinase and tenase (factor IXa/VIIIa) complexes generating large amounts of (local) thrombin [43,44] (Figure 1).…”
Section: Procoagulant Cryopreserved Plateletsmentioning
confidence: 99%
“…Amplification follows when adherent platelets sense the small amounts of thrombin via G-protein coupled protease-activated receptors (PAR) that induce a positive feedback loop in the platelet to catalyze factor V, VIII and XI activation on the platelet surface. In the propagation phase platelets are strongly activated and their increased surface area provides an assembly stage to scaffold prothrombinase and tenase (factor IXa/VIIIa) complexes generating large amounts of (local) thrombin [43,44] (Figure 1).…”
Section: Procoagulant Cryopreserved Plateletsmentioning
confidence: 99%
“…Electron microscopy has also been used to characterize the properties of platelet microparticles, patterns of platelet activation, as well as the structure of platelet plug formation in in vivo models [18,58,62,63]. For example, Ponomareva et al used both SEM and TEM to study the generation of microparticles from platelets in response to stimulation from adenosine diphosphate, arachidonic acid, and thrombin, and found that many microparticles were in fact smaller (less than 300 nm) than those typically able to be detected by flow cytometry [18].…”
Section: Diagnostic and Research Applications Of Electron Microscopymentioning
confidence: 99%
“…Furthermore, they found that microparticles isolated from patients with conditions such as disseminated intravascular coagulation, heparin induced thrombocytopenia, or lupus were larger and displayed pathologic properties [18]. Lastly, in an in vivo mouse model of vascular injury, Tomaiuolo et al used a combination of fluorescence microscopy and SEM to detail different levels of platelet activation within a forming thrombus, and the effects of antiplatelet agents on the hemostatic plug's architecture [63].…”
Section: Diagnostic and Research Applications Of Electron Microscopymentioning
confidence: 99%
“…Both signal types guide the adoption of several different platelet phenotypes at different times and locations in the thrombus (van der Meijden and Heemskerk 2019; Brass, Diamond, and Stalker 2016). The 'pro-hemostatic' secretion of von Willebrand Factor (vWF), fibrinogen (Fg), and fibronectin (Fn) occurs predominantly at injury site boundaries and in the extravascular portion of the plug (Tomaiuolo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This enables the build-up of a complex and anisotropic clot architecture (Brass, Diamond, and Stalker 2016). While the molecular regulation of individual components of the hemostatic system has been studied in detail, how to integrate the many fine-tuned platelet-responses at the systems level to ultimately initiate tissue healing is poorly understood, especially with regards to the role played by the rapidly changing extracellular microenvironment (Brass, Diamond, and Stalker 2016;Tomaiuolo et al 2019).…”
Section: Introductionmentioning
confidence: 99%